Classic patriarchal values and their effects on working Japanese women (2019)
This article examines how patriarchal values affect working women in Japanese society, specifically women in business and politics. This document is based on the work of previous authors that focus on the role of working women in modern Japan to establish the "end point" of this research. This document also includes the historical context from which traditional patriarchal norms originated. In addition, it examines the development and influence of these values in the following stages of women's lives: marriage, motherhood and participation in the workforce. To conclude, this document provides an idea of how marriage and motherhood often act as deterrents and obstacles to women's participation in business and politics.